Delivering information: A descriptive study of Australian women's information needs for decision-making about birth facility - Thompson Rachel; Wojcieszek Aleena M (BMC, 2012)
Abstract Background Little information is known about what information women want when choosing a birth facility. The objective of this study was to inform the development of a consumer decision support tool about birth facility by identifying the information needs of maternity care consumers in Queensland, Australia. Methods Participants were 146 women residing in both urban and rural areas of Queensland, Australia who were pregnant and/or had recently given birth. A cross-sectional survey was administered in which participants were asked to rate the importance of 42 information items to their decision-making about birth facility. Participants could also provide up to ten additional information items of interest in an open-ended question. Results On average, participants rated 30 of the 42 information items as important to decision-making about birth facility. While the majority of information items were valued by most participants, those related to policies about support people, other women's recommendations about the facility, freedom to choose one's preferred position during labour and birth, the aesthetic quality of the facility, and access to on-site neonatal intensive care were particularly widely valued. Additional items of interest frequently focused on postnatal care and support, policies related to medical intervention, and access to water immersion. Conclusions The women surveyed had significant and diverse information needs for decision-making about birth facility. These findings have immediate applications for the development of decision support tools about birth facility, and highlight the need for tools which provide a large volume of information in an accessible and user-friendly format. These findings may also be used to guide communication and information-sharing by care providers involved in counselling pregnant women and families about their options for birth facility or providing referrals to birth facilities.